Day-case open reduction for developmental dysplasia of the hip: is it safe?. (1st April 2021) - Flatman, Michael; Barkham, Ben H.; Ben David, Eyal; Yeo, Andrea; Norman, Joanne; Gelfer, Yael
Abstract : Aims: Open reduction in developmental dysplasia of the hip (DDH) is regularly performed despite screening programmes, due to failure of treatment or late presentation. A protocol for open reduction of DDH has been refined through collaboration between surgical, anaesthetic, and nursing teams to allow same day discharge. The objective of this study was to determine the safety and feasibility of performing open reduction of DDH as a day case. Methods: A prospectively collected departmental database was visited. All consecutive surgical cases of DDH between June 2015 and March 2020 were collected. Closed reductions, bilateral cases, cases requiring corrective osteotomy, and children with comorbidities were excluded. Data collected included demographics, safety outcome measures (blood loss, complications, readmission, reduction confirmation), and feasibility for discharge according to the Face Legs Activity Cry Consolidability (FLACC) pain scale. A satisfaction questionnaire was filled by the carers. Descriptive statistics were used for analysis. Results: Out of 168 consecutive DDH cases, 16 patients fit the inclusion criteria (age range 10 to 26 months, 13 female). Intraoperative blood loss ranged from "minimal" to 120 ml, and there were no complications or readmissions. The FLACC score was 0 for all patients. The carers satisfaction questionnaire expressed high satisfaction from the experience with adequate information and support provided. Conclusion: Open reduction in DDH, without corrective osteotomy, is safe and feasible to be managed as a day case procedure. It requires a clear treatment pathway, analgesia, sufficient counselling, and communication with carers. It is even more important during the COVID-19 pandemic when reduced length of hospital stay is likely to be safer for both patient and their parents. Cite this article: Bone Joint Open 2021;2(4):271–277.